Advancements in Sustainable Rubber Production: Bio-Based Alternatives and Recycling Technologies - Tejani, Jayadip GhanshyamBhai (ABC Journal of Advanced Research, 2020)
To comprehend their effects on the economy and environment and identify policy implications, the study looks at the developments in sustainable rubber manufacturing, particularly on bio-based alternatives and recycling technology. The study looks at sustainable rubber solutions’ economic viability, market potential, and environmental advantages through an extensive literature assessment and trend analysis. Significant discoveries highlight the promise of recycling technology and bio-based substitutes in lowering greenhouse gas emissions, preserving natural resources, and advancing a circular economy. On the other hand, significant obstacles to widespread implementation include regulatory backing, commercial acceptance, and technological difficulties. Policy ramifications highlight how crucial it is to have supportive laws, educate consumers, and work together to overcome these obstacles and promote structural transformation in the rubber sector. The study underscores the pressing necessity of innovation, cooperation, and regulatory intervention to fully actualize sustainable rubber production and establish a more resilient and environmentally conscious industry.